Teaching Undergraduate Students to Visualize and Communicate Public Health Data with Infographics - Shanks, Justin D.; Izumi, Betty; Sun, Christina; Martin, Allea; Byker Shanks, Carmen (Frontiers in Public Health, 2017)
The purpose of this study was to explore the degree to which an infographic assignment facilitated student learning around health science issues, as well as the ways in which the assignment was an effective teaching tool. The objectives of the assignment were to 1) understand the purposes of and potential uses for infographics, 2) cultivate creative visual communication skills, and 3) disseminate a complex health topic to diverse audiences. The infographic assignment was developed at [blinded University 1] and piloted at [blinded University 2]. Students were assigned to small groups of three or four to create an infographic focused on a health science issue. The assignment was divided into four steps: brainstorming, developing, designing, finalizing. Focus groups were conducted to assess how learning occurred throughout the assignment and identify any opportunities for modification of the assignment. This study was conducted with freshman students enrolled at [blinded University 2], a public university located in downtown [blinded city, town, USA]. Thirty four students completed the assignment and 31 students participated in one of three focus groups. Four themes emerged from focus groups: (1) Communicating Science Related Topics to Non-experts, (2) Developing Professional Skills, (3) Understanding Health Issues, and (4) Overall Experience. This article outlines the assignment, discusses focus group results, and presents assignment modifications. It is clear that the infographic assignment facilitated learning about accessing and translating data. This assignment is ideally suited for use with diverse college-age audiences in health education and health promotion fields.